ASEAN-5 forex rates and crude oil: Markov regime-switching analysis. Issue 54 (20th November 2022) - Aziz, Mukhriz Izraf Azman; Umar, Zaghum; Gubareva, Mariya; Sokolova, Tatiana; Vo, Xuan Vinh
ABSTRACT: We investigate the influence of moves in oil prices on exchange rates of Indonesia, Malaysia, the Philippines, Singapore and Thailand (the ASEAN-5 countries). We disentangle oil shocks, representing them by three components: demand shock, supply shock and risk shock, and examine their impact on the ASEAN-5 exchange rates by employing high-/low-volatility Markov regime-switching regressions for the period 2006 to Beckmann, Czudaj, and Arora 2020. We find that demand shocks make forex rates increase for net oil-producing as well as net oil-consuming economies. The impacts of supply shocks on forex rates for most economies are rather low. The risk shocks lead to depreciating effects on the ASEAN-5 currencies, supporting the notion that the open-oriented nature of ASEAN-5 economies makes them susceptible to constant fluctuations in the global oil market. Summary: We study interactions between the price of crude oil and exchange rates of the ASEAN-5 economies. We decompose changes in oil price into demand-, supply- and risk-driven components. We show non-linear interrelations between movements in forex rates and price of oil. Demand shocks appreciate forex rates for both net oil-producer and net oil-consumer economies. Supply-driven moves in oil prices exercise a marginal influence on forex rates for most countries. Risk shocks have depreciating effects on the ASEAN-5 exchange rates.